Short-term safety outcomes of mastectomy and immediate implant-based breast reconstruction with and without mesh (iBRA): a multicentre, prospective cohort study. Issue 2 (February 2019) - Potter, Shelley; Conroy, Elizabeth J; Cutress, Ramsey I; Williamson, Paula R; Whisker, Lisa; Thrush, Steven; Skillman, Joanna; Barnes, Nicola L P; Mylvaganam, Senthurun; Teasdale, Elisabeth; Jain, Abhilash; Gardiner, Matthew D; et al.
Summary: Background: Use of biological or synthetic mesh might improve outcomes of immediate implant-based breast reconstruction—breast reconstruction with implants or expanders at the time of mastectomy—but there is a lack of high-quality evidence to support the safety or effectiveness of the technique. We aimed to establish the short-term safety of immediate implant-based breast reconstruction performed with and without mesh, to inform the feasibility of undertaking a future randomised clinical trial comparing different breast reconstruction techniques. Methods: In this prospective, multicentre cohort study, we consecutively recruited women aged 16 years or older who had any type of immediate implant-based breast reconstruction for malignancy or risk reduction, with any technique, at 81 participating breast and plastic surgical units in the UK. Data about patient demographics and operative, oncological, and complication details were collected before and after surgery. Outcomes of interest were implant loss (defined as unplanned removal of the expander or implant), infection requiring treatment with antibiotics or surgery, unplanned return to theatre, and unplanned re-admission to hospital for complications of reconstructive surgery, up to 3 months after reconstruction and assessed by clinical review or patient self-report. Follow-up is complete. The study is registered with the ISRCTN Registry, number ISRCTN37664281. Findings: Between Feb 1, 2014, and June 30, 2016, 2108 patients had 2655 mastectomies with immediate implant-based breast reconstruction at 81 units across the UK. 1650 (78%) patients had planned single-stage reconstructions (including 12 patients who had a different technique per breast). 1376 (65%) patients had reconstruction with biological (1133 [54%]) or synthetic (243 [12%]) mesh, 181 (9%) had non-mesh submuscular or subfascial implants, 440 (21%) had dermal sling implants, 42 (2%) had pre-pectoral implants, and 79 (4%) had other or a combination of implants. 3-month outcome data were available for 2081 (99%) patients. Of these patients, 182 (9%, 95% CI 8–10) experienced implant loss, 372 (18%, 16–20) required re-admission to hospital, and 370 (18%, 16–20) required return to theatre for complications within 3 months of their initial surgery. 522 (25%, 95% CI 23–27) patients required treatment for an infection. The rates of all of these complications are higher than those in the National Quality Standards (<5% for re-operation, re-admission, and implant loss, and <10% for infection). Interpretation: Complications after immediate implant-based breast reconstruction are higher than recommended by national standards. A randomised clinical trial is needed to establish the optimal approach to immediate implant-based breast reconstruction. Funding: National Institute for Health Research, Association of Breast Surgery, and British Association of Plastic, Reconstructive and Aesthetic Surgeons.